Beneficial Effects of Castanea sativa Wood Extract on the Human Body and Possible Food and Pharmaceutical Applications - Žitek Makoter, Taja; Tancer Verboten, Mojca; Mirt, Ivan; Zupančić, Katarina; Cör Andrejč, Darija; Knez, Željko; Knez Marevci, Maša (Plants (Basel), 2024)
The aim of this review was to investigate the potential use of Castanea sativa wood extract as a food supplement and to evaluate its beneficial properties for human health. The results of the limited amount of studies suggest promising properties, including potential anti-inflammatory effects. The literature indicates that the extract, which is rich in bioactive compounds such as tannins, offers promising therapeutic possibilities for the treatment of conditions associated with chronic inflammation. Consequently, interest in its use in food and pharmaceuticals is growing. Phytochemical studies have reported antioxidant and antimicrobial activities, and anti-inflammatory, anticancer, hypolipidemic, hypoglycemic, and neuroprotective activities. A suitable extraction method and solvent is crucial for the isolation of bioactive compounds, being green extraction technologies outstanding for the industrial recovery of chestnut wood’s bioactive compounds. Nevertheless, it is important to emphasize the importance of adhering to regulatory guidelines and obtaining the necessary approvals from regulatory authorities to ensure product safety and compliance. The regulation of herbal medicinal products with proven efficacy and traditional herbal medicinal products is well defined, monitored by authorized bodies, and subject to strict control measures. It is noteworthy that medicinal products are subject to stringent quality testing to ensure safety and efficacy in use, whereas there are no comparable regulatory standards and specific labeling requirements for dietary supplements. When using herbal products, compliance with established standards in health research is essential.